2021
DOI: 10.3390/geosciences11010022
|View full text |Cite
|
Sign up to set email alerts
|

A Fluid Dynamics Approach for Assessing the Intelligent Geomorphic Design of the Japanese Pufferfish Nest

Abstract: Research into the geometric nests built by white-spotted pufferfish indicated the nest’s potential for flow control and reduction in flow velocity. However, studies to date have only focused on the construction process and behaviour of the male pufferfish. Hence, the form and functions of the unique features of the nest remain unclear. The present study aims to explore the flow features most useful in understanding the habitat conditions of the nest through a combination of photogrammetric reconstructions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Digital photogrammetry techniques allow accurate modeling of 3D space from 2D images [9]. Based on existing images, digital photogrammetry techniques are used for the 3D reconstruction of nest images [7]. After comparing the data and information, it is found that the results of this modeling technique are satisfactory.…”
Section: Construction Of Nest Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Digital photogrammetry techniques allow accurate modeling of 3D space from 2D images [9]. Based on existing images, digital photogrammetry techniques are used for the 3D reconstruction of nest images [7]. After comparing the data and information, it is found that the results of this modeling technique are satisfactory.…”
Section: Construction Of Nest Geometrymentioning
confidence: 99%
“…Based on the exciting research [7,9], the entire outer circular radius of the nest is set at 918 mm, and the radius of the center region (living area) is set at 306 mm (one-third of the outer circular radius). As the center region is lower than the seabed, a reference plane is set below the seabed by 40 mm.…”
Section: Construction Of Nest Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Shameem et al . reconstructed a 3D model of a mystery circle to explore the flow features with 2D computational fluid dynamic simulations 8 . Since our model has already been quantified as 3D data, computational fluid analysis can be immediately performed using this data, and the structural features of the mystery circle are expected to be applied in a wide range of fields, such as architecture and engineering, via biomimetics.…”
Section: Background and Summarymentioning
confidence: 99%
“…Shameem et al . reconstructed a 3D model of a mystery circle for computational fluid dynamic simulations 8 ; however, the 3D data is not published anywhere. They used a commercially available video and obtained a sequence of 23 images for the 3D reconstruction, where estimated values of the global scale were used.…”
Section: Technical Validationmentioning
confidence: 99%